59.9k views
0 votes
If f(x) = 3x + 10x and g(x) = 2x - 4, find (f- g)(x).

O A. 15x-4
B. 3X + 8x+4
O c. 3* – 8x+4
D. 3% + 12x-4

If f(x) = 3x + 10x and g(x) = 2x - 4, find (f- g)(x). O A. 15x-4 B. 3X + 8x+4 O c-example-1
User Cowirrie
by
4.7k points

2 Answers

4 votes

Answer:

B. 3ˣ + 8x + 4

General Formulas and Concepts:

Pre-Algebra

  • Distributive Property

Algebra I

  • Terms/Coefficients
  • Functions
  • Function Notation

Explanation:

Step 1: Define

Identify

f(x) = 3ˣ + 10x

g(x) = 2x - 4

Step 2: Find

  1. Substitute in function values: (f - g)(x) = 3ˣ + 10x - (2x - 4)
  2. [Distributive Property] Distribute negative: (f - g)(x) = 3ˣ + 10x - 2x + 4
  3. Combine like terms: (f - g)(x) = 3ˣ + 8x + 4
User Tarun Khurana
by
5.7k points
2 votes

Answer:

3^x+8x+4

Explanation:

f(x) = 3^x + 10x

g(x) = 2x - 4

(f- g)(x)=3^x + 10x - (2x - 4)

Distribute the minus sign

(f- g)(x)=3^x + 10x - 2x + 4

Combine like terms

3^x+8x+4

User Russell Myers
by
4.3k points